Optimalisasi Pola Operasi Pembebanan 20 KV Rao-Kota Nopan Untuk Mengatasi Drop Tegangan Dan Meningkatkan Penjualan - Andi Pratama; Habibullah Habibullah (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
ULP Lubuk Sikaping has two main sources to supply its working area, namely from the Padang Luar Substation (GI) and GI Simpang Empat. Along with the increasing use of electricity in its working area, the main problem faced by the ULP Lubuk Sikaping at this time is the voltage drop at the Rao Substation (GH) which is the farthest GH in the ULP Lubuk Sikaping working area. Due to the increase in the use of electricity while there is no addition to the source, GH Rao as the most remote area will experience the largest voltage drop. Moreover, when there is a disturbance in one of the main sources, at the Peak Load Time (WPB) ULP Lubuk Sikaping experiences a very large voltage drop and must release a load of 90 Ampere. This greatly affects the sale of electrical energy at ULP Lubuk Sikaping. There are several ways to overcome this problem, the first is the construction of a substation at ULP Lubuk Sikaping, but because the construction of a substation requires a large amount of money and takes a long time, the right step to be taken is the interconnection of Rao-Kota Nopan (ROPAN).